2016
DOI: 10.1002/mds.26713
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa modulates small‐world architecture of functional brain networks in Parkinson's disease

Abstract: Background PD is associated with disrupted connectivity to a large number of distributed brain regions. How the disease alters the functional topological organization of the brain, however, remains poorly understood. Furthermore, how levodopa modulates network topology in PD is largely unknown. Objectives We used resting state functional MRI (rsfMRI) and graph theory to determine how small-world architecture is altered in PD and affected by levodopa administration. Methods Twenty-one PD patients and 20 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 50 publications
8
71
0
Order By: Relevance
“…In fact, a recent study investigated the functional reorganization of ten brain networks composed of 226 nodes in 19 cognitively intact PD patients on and off medication (Berman et al, 2016). PD patients off medication did not show a significant change in global efficiency or overall local efficiency compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study investigated the functional reorganization of ten brain networks composed of 226 nodes in 19 cognitively intact PD patients on and off medication (Berman et al, 2016). PD patients off medication did not show a significant change in global efficiency or overall local efficiency compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have employed large-scale graph theory-based network methods using rs-fMRI in PD. These studies reported abnormalities in global and local network properties within the studied networks which also correlated with disease severity and cognitive deficits (Berman et al, 2016; Göttlich et al, 2013; Lebedev et al, 2014; Skidmore et al, 2011; Tinaz et al, 2016). …”
Section: Introductionmentioning
confidence: 90%
“…By contrast, according to small-scale network architectures [77] [78], network connectivity is dependent on the modularity of neural systems. As the number of impulses pending processing increase at the synapse with decreasing the modularity, the network connectivity is improved at the cost of metabolic stress [77] [79]. Hence, connectivity and metabolic cost are counterbalanced.…”
Section: Personal Differencesmentioning
confidence: 99%
“…Using Rs-fMRI and graph theory, researchers have explored PD-related abnormal functional brain network in PD, including topological architecture [6,7] and spontaneous brain activity [8]. For example, PD patients exhibit marked decrease in nodal and global efficiency [9], local efficiency, and local clustering coefficient [10].…”
Section: Introductionmentioning
confidence: 99%